PSYCHOLOGICAL VARIABLES OF ATTITUDE TOWARDS VACCINATION AGAINST COVID-19 - Enikolopov, S.N.; Boyko, O.M.; Medvedeva, T.I.; Vorontsova, O.Yu.; Kazmina, O.Yu. (Modern Psychology, 2021)
Vaccination is an effective way to control the infection. Aim of the study was to investigate the psychological variables associated with attitude towards coping with the pandemic by vaccination. Materials: the data of an Internet- survey of 1336 people. Methods: SCL-90-R, CTI, COPE, "Moral dilemmas" were used, the attitude was assessed according to the question. The responses received, in accordance with the activity of the subject, were divided into two blocks: "vaccination" / "overcoming the situation with the help of external circumstances." Results: "vaccination" attitude is more typical for men, asso- ciated with perception of danger of COVID-19, with more careful observance of anti-epidemic rules, the need for creativity, low paranoia, a low sense of hopelessness of the future, less indicators of categorycal thinking (CTI). In the field of coping strategies, this social attitude is positively correlated with plan- ning, concentration on emotions, with the use of instrumental and emotional social support. There are also positive links with personal choices in "Moral Modern Psychology Scientific Bulletin 2021, N2(9) 158 Dilemmas".Conclusions: the attitude of vaccination as a solution to the COVID- 19 pandemic is associated with a proactive personal social position and the availability of mental resources.